Initial misdiagnosis to a revised diagnosis of pulmonary paragonimiasis with elevated serum immunoglobulin G4 concentrations: a case report - Pengyan Yin; Miaohui Duan; Lingyao Deng; Tianli Li; Xuan Huang; Raohong Fang; Hailong Li; Binliang Bai (Journal of International Medical Research)
An elevation in serum immunoglobulin (Ig) G4 concentrations at only one time point is not a definitive diagnostic marker for IgG4-related diseases. We report two cases of pulmonary paragonimiasis with elevated serum IgG4 concentrations. Patient 1 was a woman in her late 40s with cough and dyspnea for 1 week. Patient 2 was a woman in her late 60s with a cough, bloody sputum, chest pain, and wheezing for over 1 month. Patient 1 had eosinophilia, high IgE, IgG, and IgG4 concentrations, right pleural effusion, and lung lesions, resembling tuberculosis. Patient 2 had cavitary lung lesions, pleural involvement, and eosinophilia, and high IgE, IgG, and IgG4 concentrations, with a history of eating raw river crabs. Both patients tested positive for Paragonimus antibodies. Patient 1 received 2 months of anti-parasitic treatment, while Patient 2 had 1 week of treatment. Patient 2 showed improvement and was discharged with normalized Ig concentrations. Increased serum IgG4 concentrations, in conjunction with elevated concentrations of IgG, IgE and eosinophil counts, and a history of travel or residence in areas endemic for paragonimiasis, can be used to distinguish pulmonary paragonimiasis from other etiologies of pneumonia.